New mechanisms for old drugs: Insights into DNA-unrelated effects of platinum compounds and drug resistance determinants. (May 2015) - Gatti, Laura; Cassinelli, Giuliana; Zaffaroni, Nadia; Lanzi, Cinzia; Perego, Paola
Abstract: Platinum drugs have been widely used for the treatment of several solid tumors. Although DNA has been recognized as the primary cellular target for these agents, there are unresolved issues concerning their effects and the molecular mechanisms underlying the antitumor efficacy. These cytotoxic agents interact with sub-cellular compartments other than the nucleus. Here, we review how such emerging phenomena contribute to the pharmacologic activity as well as to drug resistance phenotypes. DNA-unrelated effects of platinum drugs involve alterations at the plasma membrane and in endo-lysosomal compartments. A direct interaction with the mitochondria also appears to be implicated in drug-induced cell death. Moreover, the pioneering work of a few groups has shown that platinum drugs can act on the tumor microenvironment as well, and potentiate antitumor activity of the immune system. These poorly understood aspects of platinum drug activity sites may be harnessed to enhance their antitumor efficacy. A complete understanding of DNA-unrelated effects of platinum compounds might reveal new aspects of drug resistance allowing the implementation of the antitumor therapeutic efficacy of platinum compound-based regimens and minimization of their toxic side effects.